THE MAIN IDEA OF THE DEVELOPMENT OF PHYSICAL EDUCATION IN THE NATIONAL HISTORY OF EDUCATION (END OF XVII - BEGINNING OF XX CENTURIES) - Yulia I. Zhuravleva (Вестник Северо-Кавказского федерального университета, 2022)
The article traces the emergence of the idea of development of physical education in the domestic pedagogy late XVII - early XX centuries . Based on the analysis of works of Russian scientists, artists and politicians found that Russian pedagogy sought to define the content and means of physical education and tempering in accordance with age- especially the human body. The author characterizes the development ideas of physical education, points to a crucial feature of the formation of physical training of children in Russia as medical control over the sports activities of the population. The author highlights the most important historical achievements that have occurred during the formation of the national physical education (end of XVII - beginning of XX centuries).